Strategi Pemasaran Produk Kecantikan Melalui Media Sosial Intagram - Ayumas Harum Sawitri (Jurnal Manajemen dan Bisnis, 2015)
This study aims to determine the marketing strategy used by sellers of beauty productsthrough social media instagram. This research was conducted by interview and observationtechniques to the fifth online shop is @Angels_cherryl, @Pinkbubbleshop, @Bshop,@Ellyyeppo and @Minishoponline. Measured from 7p marketing strategy marketing mix(product, price, place, promotion, people, physical evidence, and process) and clarified theSTP marketing strategy (segmentation, targets, and position). From interviews andobservations that have been made can be seen that the five online shops 7p implementingmarketing mix well and use STP marketing strategy in accordance with the products it sellsin order to market their products well.Keywords: Electronic marketing, 7pmarketing mix, marketing strategies STP and socialmedia Instagram